Cloudy with a chance of meatballs - Marsden, Pam.; Lord, Phil, 1977-; Miller, Chris, 1975-; Hader, Bill, 1978-; Faris, Anna, 1976-; Caan, James; Samberg, Andy, 1978-; Campbell, Bruce, 1958-; Mr. T.; Thompson, Bobb'e J.; Bratt, Benjamin, 1963-; Harris, Neil Patrick, 1973-; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2010)
Flint Lockwood is a young inventor. In a town where food drops from the sky like rain, Flint hopes to create something that will change everyone's life. However, when the weather takes a turn for the worse, the residents of the town of Chewandswallow will find their eating habits have drastically changed.
Title from container.
Based on the book by Judi Barrett and Ron Barrett.
Originally released as a motion picture in 2009.
Special features: directors' commentary with Bill Hader; DVD-ROM link to exclusive online fun.
Original music, Mark Mothersbaugh.
Voices: Bill Hader, Anna Faris, James Caan, Andy Samberg, Bruce Campbell, Mr. T, Bobb'e J. Thompson, Benjamin Bratt, Neil Patrick Harris, Al Roker, Lauren Graham, Will Forte, Peter Siragusa, Angela Shelton.
Keywords: Inventors -- Drama; Television weathercasters -- Drama; Bullying -- Drama; Police -- Drama; Food habits -- Drama; Fantasy films; Comedy films; Action and adventure films; Children's films; Animated films; Feature films; Films for the hearing impaired